(untitled) (Jurnal Ipteks Terapan, 2023)
The reason is to examine and dissect the impact of the variables studied on the value of the company in forming basic and chemical businesses listed on the Indonesia Stock Exchange for the 2018-2020 period, either for themselves or for all of them. The number studied was 79 basic and chemical businesses on the IDX and used a purposive testing method to obtain information from 29 organizations with a total of 87 data. The statistical method is multiple linear regression analysis. The t test, namely Working Capital Turnover, Profitability, and Company Size have an impact on company value, while Capital Structure has no impact on company value. F Test, Capital Structure, Working Capital Turnover, Profitability, and Company Size have an impact on company value. The coefficient of determination is 29.3 % while the remaining 70.7% is explained by other variables not examined in this study